PENGARUH SUBSTITUSI SILASE TEPUNG BULU AYAM DALAM PAKAN BUATAN TERHADAP PERTUMBUHAN DAN PEMANFAATAN PAKAN IKAN NILA GIFT (Oreochromis niloticus) - Nurhayati, Wahyu; Rachmawati, Diana; Samidjan, Istiyanto (Journal of Aquaculture Management and Technology, 2017)
Tepung ikan merupakan bahan baku utama yang umum digunakan dalam pakan ikan.Tepung bulu ayam adalah salah satu solusi untuk pengganti tepung ikan karena memiliki protein yang tinggi, namun dalam pengaplikasiannya tepung bulu ayam harus difermentasi menggunakan mikroorganisme Saccharomyces sp. agar menghasilkan enzim protease sehingga tepung bulu ayam dapat lebih mudah dicerna oleh ikan. Penelitian ini bertujuan mengetahui pengaruh subtitusi tepung ikan dengan silase tepung bulu ayam pada pakan buatan terhadap pertumbuhan relatif dan kelulushidupan ikan nila gift (O. niloticus), seta mengetahui komposisi terbaik yang memberikan pertumbuhan relatif dan kelulushidupan terbaik pada ikan nila gift (O. niloticus). Ikan uji yang digunakan adalah benih ikan nila gift (O. niloticus) dengan bobot rata-rata 2,83±0,13g/ekor dan padat tebar 25ekor/m3. Penelitian ini menggunakan metode eksperimental dengan Rancangan Acak Lengkap 5 perlakuan dan 3 kali ulangan. Perlakuan dalam penelitian ini: perlakuan A (0% silase tepung bulu ayam), B (25% silase tepung bulu ayam), C (50% silase tepung bulu ayam) dan D (75% silase tepung bulu ayam), dan perlakuan E (100% silase tepung bulu ayam). Data yang diamati meliputi laju pertumbuhan relatif (RGR), efisiensi pemanfaatan pakan (EPP) dan rasio konversi pakan (FCR). Hasil penelitian menunjukkan bahwa silase tepung bulu ayam dalam pakan buatan memberikan pengaruh sangat nyata (P<0,01) terhadap RGR, EPP dan FCR. Dosis terbaik perlakuan B 25% silase tepung bulu ayam mampu menghasilkan RGR, EPP dan FCR masing-masing sebesar 3,42%/hari, 78,32% dan 1,18. Feathers meal is one of the solutions to replace fish meal because higher protein, but to apply feathers meal must trhough fermentation using Saccharomyces sp. microorganism in order to produce proteases so feathers meal can more digested by fish.This study’s purpose was to know the effect of fish meal substitution with a feather meal silage on artificial feed to the growth and survival rate gift tilapia (O. niloticus), also know the best composition substitution that provides the relative growth and best survival rate on larasati tilapia (O. niloticus). The fish samples used are gift tilapia (O. niloticus) with an average weight of 2,83±0,13g/fish and stocking density of 25 fish/m3 of water. This research used experimental method completely randomized design with 5 treatments and 3 repetitions. The treatment in this study: treatment A (0% flour feathers meal silage), B (25% flour feathers meal silage), C (50% flour feathers meal silage) and D (75% flour feathers meal silage), and treatment E (100% flour feather meal silage). Data observed relative growth rate (RGR), efficiency of feed utilization (EPP) and feed convertion ratio (FCR). Results showed that the feather meal silage in artificial feed provides highly significant effect (P <0.01) against the RGR, EPP and FCR. Best dose treatment 25% feather meal silage are capable of generating RGR, EPP and FCR by 3,42%/day,78,32% and 1,18. Feathers meal is one of the solutions to replace fish meal because higher protein, but to apply feathers meal must trhough fermentation using Saccharomyces sp. microorganism in order to produce proteases so feathers meal can more digested by fish.This study’s purpose was to know the effect of fish meal substitution with a feather meal silage on artificial feed to the growth and survival rate gift tilapia (O. niloticus), also know the best composition substitution that provides the relative growth and best survival rate on larasati tilapia (O. niloticus). The fish samples used are gift tilapia (O. niloticus) with an average weight of 2,83±0,13g/fish and stocking density of 25 fish/m3 of water. This research used experimental method completely randomized design with 5 treatments and 3 repetitions. The treatment in this study: treatment A (0% flour feathers meal silage), B (25% flour feathers meal silage), C (50% flour feathers meal silage) and D (75% flour feathers meal silage), and treatment E (100% flour feather meal silage). Data observed relative growth rate (RGR), efficiency of feed utilization (EPP) and feed convertion ratio (FCR). Results showed that the feather meal silage in artificial feed provides highly significant effect (P <0.01) against the RGR, EPP and FCR. Best dose treatment 25% feather meal silage are capable of generating RGR, EPP and FCR by 3,42%/day,78,32% and 1,18.